2007
DOI: 10.2967/jnumed.107.043406
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET Can Replace Conventional Work-up in Primary M Staging of Nonkeratinizing Nasopharyngeal Carcinoma

Abstract: Conventional work-up (CWU) with chest radiography, abdominal ultrasonography, and skeletal scintigraphy has limited value in M staging of nonkeratinizing nasopharyngeal carcinoma (NPC). Our aim was to evaluate whether 18 F-FDG PET could replace CWU by comparing their diagnostic efficacies. Methods: Patients with histologically proven nonkeratinizing NPC and no prior treatment were prospectively enrolled. All study participants underwent CWU and 18 F-FDG PET for primary M staging. Distant metastasis was conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 19 publications
1
76
0
Order By: Relevance
“…The histopathological results could be obtained by biopsy or surgical excision. 10,26 In addition, some information about scanning technique is also presented in Table 1. Only four studies used PET, while all the rest used PET/CT.…”
Section: Literature Search and Study Design Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The histopathological results could be obtained by biopsy or surgical excision. 10,26 In addition, some information about scanning technique is also presented in Table 1. Only four studies used PET, while all the rest used PET/CT.…”
Section: Literature Search and Study Design Characteristicsmentioning
confidence: 99%
“…No study reported that the reference standard was masked to the index test result (Item 11), and the index test was masked to the reference standard (Item 10) in 12 studies. 10,14,15,19,22,[24][25][26][27][30][31][32] The reporting of uninterpretable results (Item 13) and explanation of withdrawals from the study (Item 14) were presented in 12 studies 10,12,14,15,[19][20][21]25,28,[30][31][32] and 4 studies 10,14,26,27 , respectively.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional workups, including physical examinations, endoscopy, computerized tomography (CT) scans, magnetic resonance imaging (MRI), chest radiography, whole-body bone scans, and abdominal sonography, have limited sensitivity and specificity in the early diagnosis of recurrent NPC. Recently, functional imaging with 18 F-fluoro-2-deoxy-D-glucose ( 18 F-FDG) positron emission tomography (PET) scans or PET/CT scans has demonstrated encouraging efficacy in NPC staging, [1][2][3][4][5][6] response evaluation, [7][8][9] and relapse detection. [10][11][12][13] Another important advance in NPC is the quantification of plasma EBV DNA with real-time quantitative polymerase chain reaction (rt-qPCR), which reportedly is a useful tool for the detection, monitoring, and prognostic prediction in NPC.…”
mentioning
confidence: 99%